A rare case of cutaneous collagenous vasculopathy. (15th April 2015) - Meah, Nekma; Khirwadkar, Nitin; Ellison, Judith
Abstract: Cutaneous collagenous vasculopathy is a rare microangiopathy first described by Salama and Rosenthal in 2000. Several cases have been reported to date, describing distinct histological findings of thick hyaline collagenous blood vessel walls in the superficial dermis. Clinical confusion can arise with generalised essential telangiectasia. We report a case occurring in a 76‐year‐old woman who presented with a 2‐year history of a telangiectatic rash progressing from her knees upwards. The diagnosis was confirmed on skin biopsy and treatment with pulsed dye laser was later initiated at the patient's request.